Optimization and Characterization Cellulose Content of Cocoa Pod Husk from Cocoa Fermentation Center in Gunung Kidul Regency, Indonesia Through The Extraction Process - Amrillah, Nafira Alfi Zaini; Hanum, Farrah Fadhillah; Rahayu, Aster; BalqisViratu Hapsari, Alliya; Nuraini (Sains Natural: Journal of Biology and Chemistry, 2024)
Lignocellulose comprises three biopolymers, cellulose, hemicellulose, and lignin that form a complex composite structure. Cellulose, as a biopolymer possesses notable properties including biocompatibility, biodegradability and economic viability. Gunung Kidul, one of the areas in Indonesia, precisely in Yogyakarta, where the population is known to live as cocoa farmers, so the potential for cocoa husks production is quite large. One way to obtain cellulose is by extracting the cacao husks from Gunung Kidul Cocoa Fermentation Center. Cellulose extraction were carried out through two main stages: alkaline delignification and bleaching. Based on the FTIR characterization results, the cocoa skins from Gunung Kidul Fermentation Center have the potential to separate cellulose from lignin and hemicellulose, which is shown in the presence of the function groups O-H, CH2, and C=O. So, the study aimed to get the optimum condition of the cellulose through several variations of the alkaline (NaOH and KOH), and the type of bleaching reagent (NaOCl and H2O2). The concentration of H2O2 (10%, 20%, 30% and 40%). The potential for cellulose can be developed and modified into nanocellulose in the future perspective.